Нелінійні ефекти у фізиці та демографії - Weiland, J.; Rafiq, T. (Publishing house "Academperiodika", 2022)
Nonlinearities appear in almost all systems. Earlier, we focused on those in plasmas, ionospheric scattering, and the world population. As turned out, the estimate of the population growth made in 1974 is in astonishing agreement with the United Nations estimates and agrees with our present data to within 2%. A particularly important role, both for the population evolution and wave interaction in plasmas, is played by non-Markovian effects (effects depending on the past time). For the population growth, this occurs due to a delay of one generation in the set of population limiting actions, while, for plasmas, it is caused by nonlinear frequency shifts.